STUDI PENDAHULUAN: RESPON TINGKAH LAKU KEPITING TAPAL KUDA (Tachypleus gigas) TERHADAP LAMPU LED HIJAU - Fahresa Nugraheni Supadminingsih; Mochmamad Riyanto; Ronny Irawan Wahju (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2021)
The trilobite larva of horseshoe crab were tested to the light color, where the response of adult horseshoe crabs to green LED lights is unknown. This study aimed to observe the behavioral response of adult horseshoe crab towards green LED lights. The method used in this study was an experimental laboratory with 22 individuals T.gigas with a total length ±34 cm in certain criteria such as having hard carapace, no shell damage, no molting, and not in the spawning phase. The experiment was carried out in 82 repetitions in artificial ponds and observed under infrared camera. The data was collected by number of responses, time, and patterns. The results showed that 77% horseshoe crabs gave a positive response to light and 23% gave a positive response to dark areas. Horseshoe crab pattern to light response is divided into Straight to Light (41), Side to light (9), Ligth to dark (13) and Straight to dark (12), Side to dark (5) and dark to light (2). The fastest direct straight response is that LED lights that attract horseshoe crabs move quickly and respond immediately Straight to Light with is 18.66 sec/m. This study shows that the adult stage have positive phototaxis and attract to green LED lights by giving faster time with direct response patterns.